A Review on Drug Delivery System for Tumor Therapy - Guoxiang Liu; Lina Yang; Guang Chen; Fenghua Xu; Fanghao Yang; Huaxin Yu; Lingne Li; Xiaolei Dong; Jingjing Han; Can Cao; Jingyu Qi; Junzhe Su; et al. (Frontiers Media S.A., 2021)
In recent years, with the development of nanomaterials, the research of drug delivery systems has become a new field of cancer therapy. Compared with conventional antitumor drugs, drug delivery systems such as drug nanoparticles (NPs) are expected to have more advantages in antineoplastic effects, including easy preparation, high efficiency, low toxicity, especially active tumor-targeting ability. Drug delivery systems are usually composed of delivery carriers, antitumor drugs, and even target molecules. At present, there are few comprehensive reports on a summary of drug delivery systems applied for tumor therapy. This review introduces the preparation, characteristics, and applications of several common delivery carriers and expounds the antitumor mechanism of different antitumor drugs in delivery carriers in detail which provides a more theoretical basis for clinical application of personalized cancer nanomedicine in the future.